From individual resilience to collective response: reframing ecological emotions as catalysts for holistic environmental engagement - Qiu, Shicun; Qiu, Jiacun (Frontiers in Psychology, 2024)
The ongoing international study on the mental health implications of climate change has prompted a deeper exploration of ecological emotions such as eco-anxiety, eco-worry and eco-grief, which are associated with environmental degradation and the escalating climate crisis. Although psychological and mental health literature has mainly presented preliminary conceptual analyses, the understanding of ecological emotions remains unclear.This narrative review aims to clarify the definition, highlight precipitating factors, and outline the effects of ecological emotions on mental health, emphasizing the need for thorough research to shift the nonclinical intervention approach from merely promoting individual resilience to encouraging collective engagement. Our analysis of the literature reveals that the existing theoretical framework, which predominantly focuses on bolstering individual resilience, provides only temporary relief for acute symptoms without addressing the foundational social and environmental factors that trigger these ecological emotions. We conclude that it is crucial to overcome the limitations of Western anthropocentrism's human-to-human interaction approach and embrace the unity of humans and nature to effectively manage the increasing ecological emotions. This perspective draws insights from the holistic and collective wisdom of indigenous cultures and traditional Chinese philosophy, offering a potential pathway toward maintaining a sustainable emotional balance amid the worsening global ecological turmoil.